ORTHODONTIC RETENTION: A NARRATIVE REVIEW OF CURRENT EVIDENCE ON METHODS, EFFECTIVENESS, COMPLICATIONS AND INDIVIDUALIZED RETENTION PROTOCOLS - Dec, Aleksandra (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Maintaining the results of orthodontic treatment after active therapy remains one of the most important challenges in orthodontic practice. Post-treatment changes may result from true relapse of the original malocclusion, but they may also reflect physiological changes in the dentition, periodontal tissues and craniofacial structures over time. For this reason, retention should be considered an integral part of orthodontic treatment rather than an optional final stage.Objective: The aim of this narrative review is to summarize current evidence on orthodontic retention, with particular emphasis on relapse mechanisms, fixed and removable retainers, clinical effectiveness, complications, adherence to retention protocols and factors influencing individualized retention planning.Methodology: A structured literature search was conducted in PubMed. Publications concerning orthodontic retention, post-treatment stability, orthodontic relapse, fixed and removable retainers, retainer failure, periodontal effects and retainer wear were considered. Particular attention was given to systematic reviews, meta-analyses, scoping reviews and clinically relevant studies.Results: Current evidence does not support one universally superior retention method. Fixed retainers provide continuous stabilization and reduce dependence on daily appliance wear, but they are associated with failure, debonding, wire deformation and greater hygiene demands. Removable retainers are easier to clean and monitor, but their effectiveness depends on regular wear. The optimal duration of retention remains uncertain and should be adapted to individual relapse risk.Conclusions: Retention protocols should be individualized according to malocclusion type, treatment characteristics, age, periodontal status, oral hygiene, risk of relapse, availability of follow-up care and expected adherence.